If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y = 25 + -1y Solving 6y = 25 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. 6y + y = 25 + -1y + y Combine like terms: 6y + y = 7y 7y = 25 + -1y + y Combine like terms: -1y + y = 0 7y = 25 + 0 7y = 25 Divide each side by '7'. y = 3.571428571 Simplifying y = 3.571428571
| 3x-5(x-5)=17+2x+16 | | -8(6n-1)-7n=-39-8n | | 9h+11=-5-17 | | 69=23(m+1) | | 1-2x^2(e)+2x^2(lnx)=0 | | Xdy-ydx=2dy | | X^2+12x=17 | | 4(x+4)-10=-16 | | 75+2=4(5+1) | | 56x-12x+4=86 | | -2n+20=-2(3n+8)-2n | | 6(n+4)=-10 | | W=260*2/3 | | 9x+x=3x | | 5x+4+16=1 | | 260=2l(2w•2/3) | | 6(n-5)=-33+6n | | 7+x=-3x | | (x-4)=3x+4 | | 5/10=b/2 | | 4a-135=a/4 | | -6+4(-5+4n)=11+n | | 2w-3w=8w | | 1/4y=7/8 | | 12x+18=11x-7 | | 17/18x73 | | 5x+6-11=4x+3 | | 4/3(3.14)(9)E3 | | -6x-4(-6x-3)=257 | | 260-2/3 | | 4x-1=120 | | 6x+4-2x=16 |